Development of Scratch-based Educational Games on Flat Building Materials to Train Students' Critical Thinking Skills - Yuliana; Bagas Kurnianto (Journal of Practice Learning and Educational Development, 2026)
Mathematics education in elementary schools still faces challenges in training students' critical thinking skills, especially in conceptual flat shape material that requires deep understanding. This study aims to develop and test the feasibility and effectiveness of Scratch-based educational games as interactive learning media to improve the critical thinking skills of fifth-grade students. The study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product was validated by subject matter experts and media experts before undergoing small-scale and large-scale trials. The validation results showed a feasibility percentage of 91.5% from subject matter experts and 93.3% from media experts, categorized as highly feasible. The effectiveness test showed a significance value (Sig. 2-tailed) < 0.001 on both test scales, which means there was a significant increase in students' critical thinking skills. The N-gain value in the small-scale trial was 0.5421 and in the large-scale trial was 0.5723, both of which are in the moderate category. Thus, the Scratch-based educational game is declared feasible and effective for use in mathematics learning in elementary schools.